2018
DOI: 10.1097/qad.0000000000002025
|View full text |Cite
|
Sign up to set email alerts
|

Probable antenatal depression at antiretroviral initiation and postpartum viral suppression and engagement in care

Abstract: Objective To estimate the association of probable antenatal depression with postpartum HIV care engagement among pregnant women in Malawi. Design We conducted a prospective cohort study of 299 women who were initiating antiretroviral therapy (ART) through Option B+ at a government antenatal clinic in Malawi. Methods Probable antenatal depression was assessed on the day of ART initiation with the validated Chichewa version of the Edinburgh Postnatal Depression Scale (EPDS). We estimated crude and adjusted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…While pregnancy remains an important entry point for the current global 'Treat All' strategy, there is limited information regarding longitudinal VLS in this population [3]. Research studies reporting VLS estimates at various time points in the post-partum period signal particular challenges in reaching the UNAIDS goal of 90% VLS [4][5][6][7]. Further, among the few available population level estimates, we see a similar signal with Zimbabwe reporting VLS (<1000 copies/mL) in post-partum women on ART as 81.2% (CI: 79.4−83.1) at 4-12 weeks and 85.2% (CI: 82.9−87.4) at 12 months [8] and Uganda reporting a 3 year VLS (<1000 copies/mL) among post-partum women of 76% [9].…”
Section: Introductionmentioning
confidence: 99%
“…While pregnancy remains an important entry point for the current global 'Treat All' strategy, there is limited information regarding longitudinal VLS in this population [3]. Research studies reporting VLS estimates at various time points in the post-partum period signal particular challenges in reaching the UNAIDS goal of 90% VLS [4][5][6][7]. Further, among the few available population level estimates, we see a similar signal with Zimbabwe reporting VLS (<1000 copies/mL) in post-partum women on ART as 81.2% (CI: 79.4−83.1) at 4-12 weeks and 85.2% (CI: 82.9−87.4) at 12 months [8] and Uganda reporting a 3 year VLS (<1000 copies/mL) among post-partum women of 76% [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the women choosing to participate in our interviews were more likely to be those well engaged in care; it is also possible the women felt some social desirability pressure to report good adherence for themselves, while feeling more free to note that others might have such a difficulty. One explanation, as noted by another study in Lilongwe, Malawi is that because these women are in a population with high engagement in care, PND is not associated with lower ART adherence [39]. Another explanation our study found is that during this perinatal period, women may be more motivated to adhere to ART as they want to have a healthy pregnancy and remain healthy for raising their children.…”
Section: Discussionmentioning
confidence: 52%
“…It is possible that the women choosing to participate in our interviews were more likely to be those well engaged in care; it is also possible the women felt some social desirability pressure to report good adherence for themselves, while feeling more free to note that others might have such a difficulty. One explanation, as noted by another study in Lilongwe, Malawi is that because these women are in a population with high engagement in care, PND is not associated with lower ART adherence (35). Another explanation our study found is that during this perinatal period, women may be more motivated to adhere to ART as they want to have a healthy pregnancy and remain healthy for raising their children.…”
Section: Discussionmentioning
confidence: 99%